The Role of Parents in Preventing Impact Gadget Addiction in Early Childhood - Tafrihah Tafrihah; Yuli Utanto (International Conference on Science, Education, and Technology, 2022)
This article is about the role of parents in efforts to overcome the impact of gadget addiction on children. The data in this study used previous research which was analyzed through qualitative descriptions in the literature study. This analysis is to answer several questions formulated: (1) children's activities in using gadgets at home; (2) aspects developed in the use of gadgets for children; (3) how to influence children's interactions in using gadgets. The result of this paper is the discovery of positive things that can be developed to minimize the negative impact of parental assistance, which is very decisive in suppressing the negative impact of technology use activities carried out by children throughout the day.